Answers

The Brainliest Answer!
2015-03-11T20:39:19+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Quadratic formula =  \frac{-b \pm  \sqrt{ b^{2}-4ac } }{2a}

 \frac{ \frac{3}{ \sqrt{2} }\pm \sqrt{ \frac{9}{2} }   -4( \sqrt{2)}( \frac{1}{ \sqrt{2} })  }{2( \sqrt{2})}

= \frac{ \frac{3}{ \sqrt{2}} \pm  \sqrt{ \frac{9}{2} -4 } }{2 \sqrt{2} }

= \frac{ \frac{3}{ \sqrt{2} }\pm  \sqrt{ \frac{1}{2} }  }{2 \sqrt{2} }

= \frac{ \frac{3 \pm 1}{ \sqrt{2} } }{2 \sqrt{2} }

= \frac{3\pm1}{4}

x =  \frac{3+1}{4}    x =  \frac{3-1}{4}

x = 1, 1/2
2 5 2
ok
the answer is correct na?
oh, sorry sorry.................because the correct answer is 1 and 0.5.......
ooo
tysm
2015-03-12T09:56:38+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
To solve for x:
 \sqrt{2} x^{2} - \frac{3}{ \sqrt{2} }x+ \frac{1}{ \sqrt{2} }=0\\ \\ \Rightarrow \frac{1}{ \sqrt{2} }(2 x^{2} -3x+1)=0\\ \\ \Rightarrow2 x^{2} -3x+1= \sqrt{2} \times 0=0 \\ \\ \Rightarrow 2 x^{2} -2x-x+1=0\\ \\ \Rightarrow 2 x(x-1)-1(x-1)=0\\ \\ \Rightarrow (2x-1)(x-1)=0 \\ \\ \Rightarrow 2x-1=0\ \ or\ x-1=0\\ \\ \Rightarrow 2x=1\ \ or\ x=1\\ \\ \Rightarrow x= \frac{1}{2} \ \ or\ x=1
1 5 1